Optimal commodity taxation and redistribution within households - Olivier Bargain; Olivier Donni (University College Dublin, UCD School of Economics, 2011)
Using a collective model of consumption, we characterize optimal commodity taxes aimed at targeting speci…c individuals within the household. The main message is that distortionary indirect taxation can circumvent the agency problem of the household. Essentially, taxation should discourage less the consumption of a certain group of goods: those for which the slope of the Engel curves is larger for the targeted person.
Keywords: D13; D31; D63; H21; H31; 330; optimal commodity taxation; targeting; intrahousehold distribution